Intangible Materialism : The Body, Scientific Knowledge, and the Power of Language - Schleifer, Ronald (Book collections on Project MUSE., 2009)
Taking as his point of departure Norbert Weiner's statement that information is basic to understanding materialism in our era, Ronald Schleifer shows how discoveries of modern physics have altered conceptions of matter and energy and the ways in which both information theory and the study of literature can enrich these conceptions. Expanding the reductive notion of "the material" as simply matter and energy, he formulates a new, more inclusive idea of materialism. Schleifer's project attempts to bridge the divisions between the humanities and the sciences and to create a nonreductive materialis.